Ontological deflationism: plural quantification, mereological collections, and quantifier variance - Lightfield, Ceth, author; Losonsky, Michael, advisor; Chong, Edwin K. P., committee member; Sarenac, Darko, committee member (Colorado State University. Libraries, 2011)
One criticism by deflationists about ontology is that ontological debates about composite material objects are merely verbal. That is, there is only apparent disagreement between the debating ontologists. In responding to such a deflationist view, Theodore Sider (2009) has argued that there is genuine disagreement between two ontologists concerning the ontological status of tables. In doing so, Sider has written that, using plural quantification, a mereological nihilist can grant the proposition 'There exist simples arranged tablewise' while denying the proposition 'There exist collections of simples arranged tablewise'. In the first chapter, I argue that Sider's response to the deflationist is unsuccessful for two reasons. The first is that plural quantification is not ontologically innocent. A semantic interpretation of a logical formula involving plural quantification will reveal a problematic locution, namely, 'one of them' where `them' has a collection as its referent. The second concern with Sider's response is that the predicate 'arranged tablewise' is collective rather than distributive. A collection is needed to instantiate a collective predicate; thus, a commitment to simples arranged tablewise entails a commitment to a collection of simples arranged tablewise. In responding to the ontological deflationist, Sider discusses a debate between David Lewis and Peter van Inwagen about the existence of tables where a table is interpreted as a collection of simples arranged tablewise. As part of his discussion, Sider claims that Lewis and van Inwagen agree on what counts as a table. Sider allows that the deflationist may have three candidate interpretations for what counts as a 'table', but none will support the deflationist conclusion. In the second chapter, I address each candidate interpretation: (1) using Composition as Identity - a table is simples arranged tablewise, (2) a table is a set-theoretic collection of simples arranged tablewise, and (3) using Unrestricted Composition - a table is a mereological collection of simples arranged tablewise. I argue against Lewis's argument for Composition as Identity and defend an argument by Sider in support of Unrestricted Composition. Thus, I argue that composition is unrestricted and not ontologically innocent. In doing so, I show that van Inwagen cannot grant 'There exist simples arranged tablewise' and deny the existence of tables. Thus, I show that, independent of plural quantification concerns, Sider is not successful in refuting the deflationist conclusion that the ontologists are equivocating on the word 'table'. Finally, in the third chapter, I address Sider's response to the deflationist claims that the ontologists are equivocating on the quantifier 'there exists'. I look at Sider's presentation of the argument and his response which centers on an appeal to naturalness. Relying on Eli Hirsch's defense of quantifier variance, I show that the deflationist position can be maintained if Sider's appeal to naturalness is rejected. Additionally, I argue that Sider's constructed ideal language, Ontologese, does not allow Sider to avoid the deflationist criticisms. I also address the question of whether or not the deflationist program applies not only to ontological debates, but also to meta-ontological debates. To that end, I evaluate Gerald Marsh's (2010) meta-meta-ontological discussion in which he defends a dilemma for the Hirsch-Sider debate. I argue that Marsh's defense of the dilemma is problematic, and highlight a wider concern I have about meta-meta-ontological debates. I suggest that there is a frame of reference problem and end with the skeptical conclusion that answers at the meta-meta-ontological level are dependent on the language used to frame the debate.
Keywords: mereology; quantifier variance; plural quantification; metaontology